Is ultra-violet radiation the main force shaping molecular evolution of varicella-zoster virus? - Escobar-Gutiérrez Alejandro; Anaya Luis; Vazquez-Pichardo Mauricio; Cazares Fernando; Carpio-Pedroza Juan C; Fonseca-Coronado Salvador; Rivera-Osorio Pilar; Ramírez-González José E; Ruiz-Tovar Karina; Cruz-Rivera Mayra Y; Rodríguez-Castillo Araceli; Vaughan Gilberto (Virology Journal, 2011)
Abstract Background Varicella (chickenpox) exhibits a characteristic epidemiological pattern which is associated with climate. In general, primary infections in tropical regions are comparatively less frequent among children than in temperate regions. This peculiarity regarding varicella-zoster virus (VZV) infection among certain age groups in tropical regions results in increased susceptibility during adulthood in these regions. Moreover, this disease shows a cyclic behavior in which the number of cases increases significantly during winter and spring. This observation further supports the participation of environmental factors in global epidemiology of chickenpox. However, the underlying mechanisms responsible for this distinctive disease behavior are not understood completely. In a recent publication, Philip S. Rice has put forward an interesting hypothesis suggesting that ultra-violet (UV) radiation is the major environmental factor driving the molecular evolution of VZV. Discussion While we welcomed the attempt to explain the mechanisms controlling VZV transmission and distribution, we argue that Rice's hypothesis takes lightly the circulation of the so called "temperate VZV genotypes" in tropical regions and, to certain degree, overlooks the predominance of such lineages in certain non-temperate areas. Here, we further discuss and present new information about the overwhelming dominance of temperate VZV genotypes in Mexico regardless of geographical location and climate. Summary UV radiation does not satisfactorily explain the distribution of VZV genotypes in different tropical and temperate regions of Mexico. Additionally, the cyclic behavior of varicella does not shown significant differences between regions with different climates in the country. More studies should be conducted to identify the factors directly involved in viral spreading. A better understanding of the modes of transmissions exploited by VZV and their effect on viral fitness is likely to facilitate the implementation of preventive measures for disease control.